2019
DOI: 10.1111/cpr.12730
|View full text |Cite
|
Sign up to set email alerts
|

(‐)‐Epigallocatechin gallate‐loaded polycaprolactone scaffolds fabricated using a 3D integrated moulding method alleviate immune stress and induce neurogenesis

Abstract: Objectives In peripheral neuropathy, the underlying mechanisms of nerve and muscle degeneration include chronic inflammation and oxidative stress in fibrotic tissues. (‐)‐Epigallocatechin gallate (EGCG) is a major, active component in green tea and may scavenge free radical oxygen and attenuate inflammation. Conservative treatments such as steroid injection only deal with early, asymptomatic, peripheral neuropathy. In contrast, neurolysis and nerve conduit implantation work effectively for treating advanced st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 46 publications
2
27
0
Order By: Relevance
“…We found enhanced expression of Ang-1 after treatment with EGCG in LPS-induced ALI. Similar to this, other studies showed beneficial effects on the regenerative capacity of different lung cells [ 48 , 49 ]. The effect of EGCG might be mediated through KLF4, which is a well−known regulator of stem cells and has a role in cell proliferation [ 12 , 50 ].…”
Section: Discussionsupporting
confidence: 86%
“…We found enhanced expression of Ang-1 after treatment with EGCG in LPS-induced ALI. Similar to this, other studies showed beneficial effects on the regenerative capacity of different lung cells [ 48 , 49 ]. The effect of EGCG might be mediated through KLF4, which is a well−known regulator of stem cells and has a role in cell proliferation [ 12 , 50 ].…”
Section: Discussionsupporting
confidence: 86%
“…It is biocompatible and its biodegradation products are also toxic-free in the living body. Moreover, PCL provides certain mechanical stability with its high stiffness and relatively low degradation rate 32 , 33 . Consequently, the composite scaffold guarantees long-term in vivo support of structural integrity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we analysed the ability of our green teaderived (-) -Epigallocatechin gallate-loaded NGC to scavenge free radical oxygen by examining similar biomarkers, and demonstrated the importance of rectifying the energy metabolic disturbance again [11].…”
Section: Rectification Of Energy Metabolic Disturbancementioning
confidence: 99%